SISTEM JARINGAN DISTRIBUSI AIR BERSIH PDAM TIRTA TAWAR KABUPATEN ACEH TENGAH - Zamzami Zamzami; Azmeri Azmeri; Syamsidik Syamsidik (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The provision of clean water in Takengon City, Aceh Tengah Regency is provided by PDAM Tirta Tawar, one of which is through the water network of Oregon Mendale Water Treatment Plant (IPA). However, a preliminary survey at the Oregon Mendale IPA source suggested inadequate water for the community. The aim of this research is to know the factors that must be fulfilled so that a clean water network system can run smoothly. This includes water flow, pressure and flows continuity, maximum daily factor (Fmax) and real peak factor (Fpeak) of the existing network. This study is also to understand the clean water distribution network in the Oregon Mendale IPA resource area. This research uses a descriptive method and field observation. This study suggests the following: the average water consumption is 0,426 m3/customer/day, the maximum water pressure is 1.517 m and the continuity of flow is 6 hours every day. The maximum daily factor value (Fmax) in Kecamatan Kebayakan is 1.13-1.39 and the peak hour factor (Fpeak) is 1.13-1.41. These results suggested that the existing Oregon Mendale IPA is not running optimally.